A rule based resources management for collaborative grid environments. (7th July 2008) - Herrero, Pilar; Bosque, Jose Luis; Salvadores, Manuel; Perez, Maria S.
Something that is still missing, but strongly needed, in collaborative grid environments is a stable, flexible and dynamic resource management. This management should optimise collaboration and cooperation among several resources keeping resources constraints, preconditions and rules. This paper presents how to achieve these objectives, by means of a Collaborative Awareness Management (CAM) model. CAM optimises resources collaboration, promotes resources cooperation and responds to the specific demanded circumstances. This paper also describes how this model works in some specific examples and scenarios, emphasising on how the WS-CAM Rules-Based Management Application has been designed, implemented, and validated to accomplish these purposes.